Psychological transition from meaning to sense (European Journal of Education and Psychology, 2011)
This work presents an approach aimed at modeling the sensemaking underlying psychological transition in an educational setting -though not confined to such types of setting. The psychological transition is understood as change that is to move from a state of psychological equilibrium (eg, identification with a certain vision of the world) to another. This approach is derived from our combined socio-constructivist and psychoanalytic standpoint. It distinguishes two levels of analysis: the representational content, and the shared latent affective dimension, the latter working as the symbolic frame of sensemaking. According to our model, psychological transition has to be defined as a change in the affective structure of sense. We present our theoretical model and a method of analysis following from it. In order to exemplify and to validate our approach, we examine the case of young people entering high school in Italian schools. This study depicts the students’ representations involved in role transition. It shows how, in spite of deep modifications of representations related to their entrance to the high school setting, the latent dimension of sensemaking does not change.